Crosstalk between cilia and autophagy - Morleo, Manuela (2022)
Macroautophagy/autophagy is a self-degradative process necessary for cells to maintain their energy balance during development and in response to nutrient deprivation. Autophagic processes are tightly regulated and have been found to be dysfunctional in several pathologies. Increasing experimental evidence points to the existence of an interplay between autophagy and cilia. Cilia are microtubule-based organelles protruding from the cell surface of mammalian cells that perform a variety of motile and sensory functions and, when dysfunctional, result in disorders known as ciliopathies. Indeed, selective autophagic degradation of ciliary proteins has been shown to control ciliogenesis and, conversely, cilia have been reported to control autophagy. Moreover, a growing number of players such as lysosomal and mitochondrial proteins are emerging as actors of the cilia-autophagy interplay. However, some of the published data on the cilia-autophagy axis are contradictory and indicate that we are just starting to understand the underlying molecular mechanisms. In this review, the current knowledge about this axis and challenges are discussed, as well as the implication for ciliopathies and autophagy-associated disorders.